How do dynamic financing decisions explain the behavior of dividend payout policies? An empirical study of listed Pakistani manufacturing firms - Zahid Bashir; Zulqurnain Zeeshan Rafique; Kashif Naseer Toor (Financial Internet Quarterly, 2022)
The study investigates the factors that influence dividend payout policy in public Pakistani manu- facturing companies throughout the timeframe 2010-20. Pooled OLS technique was used for regression purposes, as the majority of companies do not pay a dividend at all or do not do so regularly so all these firms were excluded from the final dataset. The study discovers that divi- dend payout in listed Pakistani manufacturing firms is significantly affected by ratio of short- debt, ratio of long-debt, ratio of total-debt, life cycle ratio and cash ratio. Similarly, short term debt ratio, ratio of long-debt and life cycle ratio, increase the dividend payout while cash ratio decreases the dividend distribution ratio for publically traded Pakistani manufacturing compa- nies. The policymakers/financial advisors and decision-makers in listed Pakistani manufacturing firms should take into consideration factors such as debt financing, life cycle ratio, and cash ratio in making their dividend policies.
Keywords: C1; C4; C8; G2; G3; L2; L6; 330; dividend policy; financing decision; debt financing; equity ratio